Improved adjuvant endocrine therapy for premenopausal women with endocrine responsive disease - Goldhirsch, Aron (Ecancermedicalscience, 2015)
Results from two randomised global trials (SOFT & TEXT) designed to newly define the most effective components of adjuvant endocrine therapy for premenopausal women with endocrine responsive disease, showed that for some, those with high risk of relapse, the use of the aromatase inhibitor exemestane together with ovarian function suppression with GnRH analogue (triptorelin) yielded the most favourable treatment outcome compared with tamoxifen. For women with low risk of relapse, treatment with tamoxifen was similar to ovarian function suppression together with either exemestane or tamoxifen. For women with intermediate risk of relapse, ovarian function suppression added to tamoxifen was not inferior to exemestane, while it resulted in superior outcomes compared to tamoxifen alone. Now, these trials provide critical information for the adjuvant treatment of premenopausal women with endocrine responsive breast cancer and are important for the development of future trials for further improvement of adjuvant endocrine therapies for the younger population.